Artificial Intelligence Advancements in the Cardiovascular Imaging of Coronary Atherosclerosis - Covas, Pedro; De Guzman, Eison; Barrows, Ian; Bradley, Andrew J.; Choi, Brian G.; Krepp, Joseph M.; Lewis, Jannet F.; Katz, Richard; Tracy, Cynthia M.; Zeman, Robert K.; Earls, James P.; Choi, Andrew D. (Frontiers in Cardiovascular Medicine, 2022)
Coronary artery disease is a leading cause of death worldwide. There has been a myriad of advancements in the field of cardiovascular imaging to aid in diagnosis, treatment, and prevention of coronary artery disease. The application of artificial intelligence in medicine, particularly in cardiovascular medicine has erupted in the past decade. This article serves to highlight the highest yield articles within cardiovascular imaging with an emphasis on coronary CT angiography methods for % stenosis evaluation and atherosclerosis quantification for the general cardiologist. The paper finally discusses the evolving paradigm of implementation of artificial intelligence in real world practice.